THE SIGNIFICANCE OF SOCIO-POLITICAL VALUES OF THE PEOPLES OF CENTRAL ASIA IN THE DEVELOPMENT OF INTERSTATE INTEGRATION RELATIONS - Isomov Mukhammadjon Kurontoevich (Modern American Journals, 2025)
The article analyzes the significance of common socio-political values of the peoples of Central Asia, such as socio-political unity, interethnic harmony and religious tolerance, mutual respect for the elderly and youth, cultural and linguistic affinity, historical unity of lifestyle and traditions, among others, which serve as fundamental socio-political factors underlying the process of strengthening and developing socio-economic and cultural interstate integration relations in the region. It is emphasized that in today’s global environment, the role of common socio-political values as an instrument of "soft power" in fostering regional solidarity is increasing, as well as their growing influence and importance in strengthening and developing economic, socio-political, and cultural ties, established on the basis of systematically implemented interstate integration relations. The article demonstrates through examples that the socio-political values of the peoples of the region contribute to sustainable development through youth policy, intercultural dialogue, digital and public diplomacy, as well as through cooperation with various civil society institutions.
Keywords: Central Asia, socio-political values, political integration, soft power, historical unity, intercultural dialogue, youth policy, historical heritage, cooperation, diplomacy, public diplomacy, social stability.